2016
DOI: 10.1038/srep23892
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA—UCA1 enhances cell proliferation and 5-fluorouracil resistance in colorectal cancer by inhibiting miR-204-5p

Abstract: Recent preliminary studies reported the in vitro tumor-promoting effects of long non-coding RNA urothelial carcinoma associated 1 (UCA1) in colorectal cancer (CRC). However, the in vivo functions and molecular mechanism of UCA1 in CRC remain unclear. Therefore, we investigated the detailed role and mechanism of UCA1 in CRC. We found that UCA1 was up-regulated in CRCs and negatively correlated with survival time in two CRC cohorts. Functional assays revealed the in vitro and in vivo growth-promoting function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
350
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(361 citation statements)
references
References 41 publications
(75 reference statements)
9
350
0
1
Order By: Relevance
“…LncRNAs (long noncoding RNAs) are broadly defined as noncoding RNA molecules longer than 200 nucleotides [20,21]. They are key elements in cell differentiation and ontogenetic process through interactions with DNA, chromatin, regulatory proteins and a variety of cellular RNA species.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs (long noncoding RNAs) are broadly defined as noncoding RNA molecules longer than 200 nucleotides [20,21]. They are key elements in cell differentiation and ontogenetic process through interactions with DNA, chromatin, regulatory proteins and a variety of cellular RNA species.…”
Section: Discussionmentioning
confidence: 99%
“…Uptake of exosomal UCA1 induced tamoxifen resistance in sensitive cancer cells (137). Even though the detailed mechanism was not revealed in this study, UCA1 was previously found to induce aggressive phenotype and drug resistance by suppression of p27 (138) or acting as sponge for miR-143 (139) and miR-204-5p (140). …”
Section: Roles Of Evs In Cancer Progressionmentioning
confidence: 75%
“…However, in one of the recent study, the presences of lncRNAs such as UCA1 and sNAR have been shown to affect the effectiveness of the 5-FU treatment. Downregulation of snaR could decrease the sensitivity towards 5-FU and drug-induced cell death in CRC cells whereas the upregulation of UCA1 in CRC reduces the sensitivity towards 5-FU and drug-induced cell death through inhibiting the activity of miR204-5p as a sponge [36,37] . Therefore, the complexity of lncRNA in the progression of cancer and its involvement in the treatment and diagnosis of cancer requires further research in order for greater understanding and its subsequent clinical translation.…”
Section: Discussionmentioning
confidence: 99%